Human Papillomavirus (Hpv) Vaccination of The Girl Child: An Intervention for Primary Prevention of Cervical Cancer in India: Life Sciences-Pediatrics - Ramesh, Shanthi; R, Somasekar; S, Sundari (International Journal of Life Science and Pharma Research, 2022)
This review gives a comprehensive account of the currently available HPV vaccines including the Nonavalent vaccine which was not covered by some articles. The review includes the current burden of cervical cancer globally and in India. It also outlines the cervical cancer elimination initiative envisaged by the National Health Mission and the World Health Organization. This review aims to highlight the importance of cervical cancer prevention through HPV vaccination and regular screening program. The Human Papillomavirus infection is an established cause of cervical cancer in women. Cervical cancer is the second leading cause of cancer deaths among women in India. India has a young population with more than 436.7 million women aged 15 years and older at risk of developing cervical cancer. There is mounting evidence that cervical cancer is highly preventable. Primary prevention can be done effectively by vaccinating adolescent girls aged 9 to 14 years with the HPV vaccine. Three HPV vaccines, namely the Bivalent, Quadrivalent, and Nonavalent, are currently licensed for use. As part of the National Health Mission, the Government of India launched for the year 2016 for the first time, a population-based prevention, screening, and control program for cervical cancer. The World Health Organization has launched a cervical cancer elimination initiative that looks forward to a cancer-free future. The review concludes that though there are challenges at every level, the solution points in only one direction. All need to work together to ensure the HPV vaccination program is included in our National Immunization Program as the top priority.